Zooming in and out of photograph: image interpolation and decimation - Sivaramalingam Thejesvi (Nanyang Technological University, 2023)
This report provides an overview of image interpolation and decimation methods, which are used to zoom in or out of digital images. The report begins by highlighting the importance of image zooming in various applications, including medical imaging and digital photography. Next, the report describes the different image decimation and interpolation methods. The strengths and limitations of the methods are covered, along with the mathematical foundation and implementation details. Additionally, the report provides a comparative analysis of the different interpolation algorithms based on visual quality and computational complexity. Overall, the report presents a comprehensive review of the quality of image interpolation and decimation methods that can aid researchers in making informed decisions on using the appropriate method for their specific application.